The MSH2 c.388_389del mutation shows a founder effect in Portuguese Lynch syndrome families. (27th December 2012) - Pinheiro, M; Pinto, C; Peixoto, A; Veiga, I; Mesquita, B; Henrique, R; Lopes, P; Sousa, O; Fragoso, M; Dias, LM; Baptista, M; Marinho, C; et al.
Abstract : The MSH2 c.388_389del mutation has occasionally been described in Lynch families worldwide. At the Portuguese Oncology Institute in Porto, Portugal, we have identified 16 seemingly unrelated families with this germline mutation. To evaluate if this alteration is a founder or a recurrent mutation we performed haplotype analysis in the 16 Portuguese index cases and 55 relatives, as well as in four index cases and 13 relatives reported from Germany, Scotland, England, and Argentina. In the Portuguese families we observed a shared haplotype of approximately 10 Mb and all were originated from the north of Portugal. These results suggest that this alteration is a founder mutation in Portugal with a relatively recent origin. In the reported families outside Portugal with this mutation different haplotype backgrounds were observed, supporting the hypothesis that it occurred de novo on multiple occasions. We also conclude that the high proportion of families with the MSH2 c.388_389del mutation indicates that screening for this alteration as a first step may be cost‐effective in the genetic testing of Lynch syndrome suspects of Portuguese ancestry, especially those originating from the north of Portugal.